Study of the Myocardial Contraction and Relaxation Velocities through Doppler Tissue Imaging Echocardiography: A New Alternative in the Assessment of the Segmental Ventricular Function - Silva,Carlos Eduardo Suaide (2002)
OBJECTIVE: Doppler tissue imaging (DTI) enables the study of the velocity of contraction and relaxation of myocardial segments. We established standards for the peak velocity of the different myocardial segments of the left ventricle in systole and diastole, and correlated them with the electrocardiogram. METHODS: We studied 35 healthy individuals (27 were male) with ages ranging from 12 to 59 years (32.9 ± 10.6). Systolic and diastolic peak velocities were assessed by Doppler tissue imaging in 12 segments of the left ventricle, establishing their mean values and the temporal correlation with the cardiac cycle. RESULTS: The means (and standard deviation) of the peak velocities in the basal, medial, and apical regions (of the septal, anterior, lateral, and posterior left ventricle walls) were respectively, in cm/s, 7.35(1.64), 5.26(1.88), and 3.33(1.58) in systole and 10.56(2.34), 7.92(2.37), and 3.98(1.64) in diastole. The mean time in which systolic peak velocity was recorded was 131.59ms (±19.12ms), and diastolic was 459.18ms (±18.13ms) based on the peak of the R wave of the electrocardiogram. CONCLUSION: In healthy individuals, maximum left ventricle segment velocities decreased from the bases to the ventricular apex, with certain proportionality between contraction and relaxation (P<0.05). The use of Doppler tissue imaging may be very helpful in detecting early alterations in ventricular contraction and relaxation.